2023
DOI: 10.1101/2023.09.29.560231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adolescent oligodendrogenesis and myelination restrict experience-dependent neuronal plasticity in adult visual cortex

Wendy Xin,
Megumi Kaneko,
Richard H. Roth
et al.

Abstract: BACKGROUNDDevelopmental myelination is a protracted process in the mammalian brain. One theory for why oligodendrocytes mature so slowly posits that myelination may stabilize neuronal circuits and temper neuronal plasticity as animals age. We tested this hypothesis in the visual cortex, which has a well-defined critical period for experience-dependent neuronal plasticity.OBJECTIVES/METHODSTo prevent myelin progression, we conditionally deleted Myrf, a transcription factor necessary for oligodendrocyte maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Astrocytes and oligodendrocytes are both born late in embryonic development, and oligodendrocyte maturation similarly mirrors the transition from critical period plasticity to stability. Indeed, a recent study found that blocking oligodendrocyte maturation was sufficient to extend ocular dominance plasticity ( Xin et al, 2023 ). While astrocytes mediate critical period closure through modulation of E/I balance and ECM composition, oligodendrocytes seem to function in parallel to ensure critical period closure.…”
Section: Glia As Mediators Of Critical Period Timingmentioning
confidence: 99%
“…Astrocytes and oligodendrocytes are both born late in embryonic development, and oligodendrocyte maturation similarly mirrors the transition from critical period plasticity to stability. Indeed, a recent study found that blocking oligodendrocyte maturation was sufficient to extend ocular dominance plasticity ( Xin et al, 2023 ). While astrocytes mediate critical period closure through modulation of E/I balance and ECM composition, oligodendrocytes seem to function in parallel to ensure critical period closure.…”
Section: Glia As Mediators Of Critical Period Timingmentioning
confidence: 99%